Emergence of Arabic New Loan Words among Yoruba Speakers in Southwestern Nigeria: A Critical Analysis (Journal of Management and Social Sciences, 2020)
Language is a social phenomenon that is used as a means of communication among the indigenous inhabitants of a particular community. It is also a significant factor and powerful tool in transmitting information, ideas, and resolutions irrespective of location, time and purpose. In this literary and linguistic analytical study, the researcher engages in analytical method in examining the rise and frequency in the use of Arabic language as a means of self–expression among Yoruba speakers in the South-Western part of Nigeria in order to suit their needs in some identified circle, clique and profession. The analysis of those words is presented and justified in the way they are used in this context. References are made to address the previous process of some loan words from Arabic to English and Yoruba languages. The findings show the emergence of new loan words from Arabic to the Yoruba language in the region and, even, English language, especially in social media contents. It is observed that if this continues, after some years, the Arabic words will become household words among Yoruba speakers or be codified as part of Yoruba and English languages. Unborn generations will, therefore, consider them as original Yoruba and/or English words instead of their Arabic origin. It is hereby recommended that the teachers of Arabic language should be observant of this rapid trend and keep eyes on this emergence for posterity reason to retain the Arabic origin of those new loan words.